2011
DOI: 10.1136/thoraxjnl-2011-200172
|View full text |Cite
|
Sign up to set email alerts
|

Do asbestos-related pleural plaques on HRCT scans cause restrictive impairment in the absence of pulmonary fibrosis?

Abstract: Background It is uncertain whether isolated pleural plaques cause functional impairment. Objective To analyse the relationship between isolated pleural plaques confirmed by CT scanning and lung function in subjects with occupational exposure to asbestos. Methods The study population consisted of 2743 subjects presenting with no parenchymal interstitial abnormalities on the high-resolution CT (HRCT) scan. Asbestos exposure was evaluated by calculation of an individual cumulative exposure index (CEI). Each subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…But these PFT results are still within normal limits, it may not have a real clinical relevance for the subjects with decreased pulmonary function. Similarly, study by Clin et al (20) showed that patients with isolated pleural plaques and/or diaphragmatic pleural plaques exhibited significant decreases in total lung capacity, FVC and FEV 1 which showed a trend towards a restrictive pattern. However, they concluded that since PFT results were within normal limits, the PFT decreases were unlikely to be of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…But these PFT results are still within normal limits, it may not have a real clinical relevance for the subjects with decreased pulmonary function. Similarly, study by Clin et al (20) showed that patients with isolated pleural plaques and/or diaphragmatic pleural plaques exhibited significant decreases in total lung capacity, FVC and FEV 1 which showed a trend towards a restrictive pattern. However, they concluded that since PFT results were within normal limits, the PFT decreases were unlikely to be of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, in the six cross-sectional studies of non-Libby populations that evaluated the association between pleural plaques and pulmonary function with adjustment for asbestos exposure (Broderick et al, 1992;Clin et al, 2011;Lilis et al, 1991;Miller et al, 1994;Oliver et al, 1988;Wang et al, 2001), results varied depending on the measure of lung function, with no consistent patterns of association with spirometric or symptom-based outcomes. Moreover, two studies did not distinguish LPT from DPT (Miller et al, 1994;Wang et al, 2001), only one used highresolution computed tomography to detect LPT (Clin et al, 2011) and all six were susceptible to residual confounding by asbestos exposure and occult parenchymal fibrosis.…”
Section: Pleural Plaques and Impairments To Lung Functionmentioning
confidence: 99%
“…Numerous studies have examined the dose-or exposureresponse relation for pleural plaques (Bar-Shai et al, 2012;Boffetta, 1998;Clin et al, 2011;Eisenhawer et al, 2014;Ehrlich et al, 1992;Finkelstein & Vingilis, 1984;Hosoda et al, 2008;Jakobsson et al, 1995;Järvholm, 1992;Karjalainen et al, 1994;Lockey et al, 2015;Mastrangelo et al, 2009;McDonald et al, 1986;Moolgavkar et al, 2014;Paris et al, 2008Paris et al, , 2009Rohs et al, 2008;Sandén & Järvholm, 1986;Shepherd et al, 1997;Soulat et al, 1999;Van Cleemput et al, 2001). Results differ among these studies, 6 but exposure variables found relevant in one or more studies include time since first exposure (TSFE), age at first exposure (Jones, 1997), type (Hillerdal, 1997;Jones, 1997;Sandén & Järvholm, 1986) and dimensions of fiber (Hillerdal, 1997;Jones, 1997), lung fiber burden (Karjalainen et al, 1994;Roberts, 1971), duration of exposure, intensity of estimated asbestos exposure and cumulative exposure (measured in various ways).…”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
“…4 LPT is associated with constricting pain 5,6 and reduced lung function. 7,8 Libby amphibole asbestos (LAA) is a mixture of amphibole fibers identified in the Rainy Creek complex and present in ore from the vermiculite mine near Libby, MT, USA. 9 Epidemiological studies of worker cohorts in Libby, MT, USA, 10,11 and Marysville, OH, USA, 12,13 exposed to LAA fibers indicate increased risk of radiographic abnormalities, and that the latency period for development of radiographic abnormalities may be relatively short (median latency of 8.6 years for pleural plaques in retrospective investigation of serial radiographs).…”
Section: Introductionmentioning
confidence: 99%